Quality of a life skills training program in Karnataka, India - a quasi experimental study - Banandur S. Pradeep; Banavaram Anniappan Arvind; Srinivas Ramaiah; Swati Shahane; Lavanya Garady; Mutharaju Arelingaiah; Gopalkrishna Gururaj; Gananatha Shetty Yekkaru (BMC, 2019)
Abstract Background Youth focused Life Skills Education and Counseling Services (YLSECS) program, trained teachers/National Service Scheme (NSS) officers to deliver Life Skills Education (LSE) and counseling services to college going youth in the state of Karnataka in India. Available evaluation of life-skills training program have neglected the recording and or reporting of outcome among those trained to implement life-skills training program. Present paper highlights the quality of YLSECS training program and change in perception among teachers/NSS-officers trained in-terms of improvement in their cognitive/affective domains. Methods YLSECS program focused on World Health Organization identified ten essential domains of life-skills. Participants of the YLSECS program were trained by adopting facilitatory approach based on the principles of Kolb's learning theory. Quasi experimental study design was used to evaluate the outcome of training among participants. Quality of the training was assessed using scoring system and change in perception was assessed using Likert scale. Statistical significance of change in perception before and after training was assessed by paired't' test for proportion. Results Overall, 792 participants rated the quality of training as either "good" or "excellent". Post-training, significant (p < 0.001) proportion of the participants reported improved awareness about life-skills (before training 49.9 to 74.4% vs post-training range from 91.6 to 95.1% for various domains). There was statistically significant (p < 0.001) increase in participants reporting "very confident" in teaching various life skill domains (before training from 22.7 to 34.2% for various domains and post-training it ranged from 65.2 to 74.7% for various domains). There was modest increase in participants reporting perceived ability to conduct life-skills workshop "without assistance" post-training (before training from 16.8 to 22.9% for various domains vs post-training ranged from 29.8 to 36.8% for various domains). Interestingly, considerable proportion of participants who prior to training reported being confident in providing life skills training (without any assistance), later (i.e post training) reported they need some/more assistance for the same. Conclusion YLSECS training program significantly improved participants knowledge and confidence in imparting life-skills and highlight the need for continued handholding of participants for effective implementation of LSE and counseling service program.